Um diagnóstico da qualidade nas empresas de tratamento térmico de moldes e matrizes - Moraes, Priscilla Aparecida Vieira de (2014)
Quality management in the thermal treatment services sector Brazil is not scientifically known. However there are indications that several quality problems occur in this segment due to a systematic quality management ineffective. The final steel quality to produce tools depends on the adequate heat treatment. The most failures occur in the properties due to the fact a treatment incorrect and inefficient heat. In this context, the present study is proposed to assess the quality management treatment in business heat from industrial tools to after comparing the surveyed companies establish a benchmarking analysis comparing with the company sector model. This current study intends to use unstructured interviews in business macro and sector analysis segment. In methodological terms the nature of the proposed research work will be characterized by literature review and case study. In order to get information about how quality management in the thermal treatment of industrial tools company, has developed a qualitative research exploratory. With the results obtained from the interviews will be made a comparison between the surveyed companies and a benchmarking analysis will be established.